Cooperation and innovation in industrial and services sectors in Brazil (Research, Society and Development, 2020)
The search for differential to deal with competitiveness and current market dynamics have led companies to innovate. From collaborations in the field of cooperation and innovation arise networks of cooperation in order to overcome the insufficiency of financial resources, human capital, knowledge and infrastructure companies, among other factors. This research aims to analyze the relations of cooperation between innovative companies, surveyed by Technological Innovation Research (PINTEC) 2008. The study can be characterized as a descriptive research based on secondary data from the IBGE / PINTEC 2008. The data were processed with the aid of SPSS (Statistical Package for Social Science) for implementation of Multivariate Analysis Cluster. The sectors with the highest levels of cooperation were: manufacture of food products, manufacture of articles of clothing and accessories, manufacture of rubber and plastic products, manufacture of metal products, machinery and equipment manufacturing, manufacturing of various products and activities of information technology services. Other findings of the survey indicate that the type of innovation is the prevailing organizational partner and most common is the national supplier.